PARADIGMA HUKUM WARIS ATAS TANAH YANG TIDAK MENGENAL DALUARSA SETELAH TERBITNYA UUPA - Sinaga, Andreas J (Universitas Katolik Santo Thomas Medan, 2020)
In litigating in the court, the Defendant usually made an exception regarding the expiration of the suing rights verjaring, known as Exeptio Temporis. In the inheritance law the Civil Code regulates the passing of verjaring, Article 835 BW That claim (heirs has the right to submit a claim to obtain his inheritance against all people who control all or part of the inheritance on the basis of rights or without basis of rights) becomes past due with the passage of thirty year, counted and the day the inheritance was opened. The emergence of Undang-Undang Nomor 5 Tahun 1960 Tentang Peraturan Dasar Pokok-Pokok Agraria (Law of Basic Rules of Agrarian Principles) eradicates dualism as long as land is enforced with customary law in addition to agrarian law based on the Civil Code, so the Law of Basic Rules of Agrarian Principles revokes the second book of the Civil Code as long as it concerns the earth, water and natural resources that contained therein because the Law of Basic Rules of Agrarian Principles accommodates customary law.